2013
DOI: 10.1093/icvts/ivt003
|View full text |Cite
|
Sign up to set email alerts
|

Left main coronary artery compression by a left sinus of Valsalva aneurysm

Abstract: Myocardial ischaemia due to extrinsic left main coronary artery compression is unusual. Most cases are related to pulmonary hypertension with severe main pulmonary artery dilatation. An extremely rare cause is a left sinus of Valsalva aneurysm (SVA). We describe the case of a patient diagnosed of left SVA after a coronary angiography and aortography, whose initial clinical manifestation was an acute coronary syndrome complicated with an out-hospital resuscitated sudden cardiac death.Keywords: Aneurysm (aortic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 6 publications
1
8
0
Order By: Relevance
“…Unruptured SOVAs typically remain asymptomatic for decades and are often discovered incidentally on echocardiography or other imaging modalities. However, large unruptured aneurysms can produce mass effect and may cause valvular dysfunction, right ventricular outflow tract obstruction, and myocardial ischemia due to compression on the origin of the main coronary arteries [6]. Nonetheless, acute symptoms usually occur in most cases of aneurysmal rupture and subsequent fistula formation to the adjacent cardiac chamber.…”
Section: Discussionmentioning
confidence: 99%
“…Unruptured SOVAs typically remain asymptomatic for decades and are often discovered incidentally on echocardiography or other imaging modalities. However, large unruptured aneurysms can produce mass effect and may cause valvular dysfunction, right ventricular outflow tract obstruction, and myocardial ischemia due to compression on the origin of the main coronary arteries [6]. Nonetheless, acute symptoms usually occur in most cases of aneurysmal rupture and subsequent fistula formation to the adjacent cardiac chamber.…”
Section: Discussionmentioning
confidence: 99%
“…[9,10,18,19] Successful surgical repair was first reported in 1957 and is recommended when the sinus grows to > 50% larger than the average size of the other two sinuses, compresses surrounding chambers or origin of the main coronary arteries, increases in consecutive echocardiograms (> 0.5 cm/year) or presents incidentally during cardiac surgery. [20][21][22][23][24][25] In order to avoid complications associated with aneurysm enlargement or endocarditis, early surgical repair has been recommended especially since this surgery is associated with low morbidity and mortality, however this has not been established in elderly patients. [9,24,26] A study involving a 33-year single center experience found patients undergoing sinus of Valsalva aneurysm repairs were more commonly males (70%) and the average age was 30 years.…”
Section: Discussionmentioning
confidence: 99%
“…Unruptured SOVAs typically remain asymptomatic for decades and are often discovered incidentally on echocardiography or other imaging modalities. However, large unruptured aneurysms can produce mass effect and may cause valvular dysfunction, right ventricular outflow tract obstruction, and myocardial ischemia due to compression on the origin of the main coronary arteries [ 5 ]. Nonetheless, acute symptoms usually occur in most cases of aneurysmal rupture and subsequent fistula formation to the adjacent cardiac chamber.…”
Section: Discussionmentioning
confidence: 99%